Brazilian farmer perception of dynamic capability and performance over the adoption of enterprise resource planning technology - Haberli Júnior, Caetano (2021)
Haberli Júnior, C., Spers, E. E., Oliveira, T., & Yanaze, M. (2020). Brazilian farmer perception of dynamic capability and performance over the adoption of enterprise resource planning technology. International Food and Agribusiness Management Review, 23(4), 515-528. https://doi.org/10.22434/IFAMR2020.0029